The Role of Tariqat Naqsabandiyah in Fostering Religious Attitudes in Santri Pondok Pesantren Darul Mutta'allimin Tanah Merah Aceh Singkil Regency - Junaidi Asryad; Muhammad Ridwan; Maritsa Ulfa Khaira (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to analyze: 1) the condition of the Darul Muta'allimin Tanah Merah Islamic boarding school in Aceh Singkil Regency, 2) the development of Tariqat Naqsyabandiah at the Darul Muta'allimin Islamic boarding school in Tanah Merah, 3) the Tariqat Naqsyabandiah method used in cultivating religious attitudes in Islamic boarding school students Darul Muta'allimin, 4) supporting and inhibiting factors in the implementation of Tariqat Naqsyabandiah in cultivating religious attitudes in students at the Darul Muta'allimin Tanah Merah Islamic boarding school. The research method used in this research is field research, namely research that aims to collect data and information from various observations in the field. The results of the research show that: 1) This Islamic boarding school has a social and religious influence on social development in the Aceh Singkil community through the activities of the Naqsyabandiyah , The existence of the Naqsyabandiyah and suluk orders at the Darul Muta'allimin Islamic Boarding School has experienced ups and downs, but the Naqsyabandiyah order still exists among the community and its existence is very well received because its aim is to get closer to Allah. Supporting factors in the implementation of Tariqat Naqsyabandiah, namely: strong will of the students, strategic location, appropriate place of prayer, well-established facilities, and Muryid and caliph who teach in earnest. Meanwhile, the inhibiting factors are: students who are sick or unhealthy and lack of enthusiasm for students in carrying out a series of activities of the Naqsyabandiyah congregation.